(−)‐Epigallocatechin‐3‐gallate and EZH2 inhibitor GSK343 have similar inhibitory effects and mechanisms of action on colorectal cancer cells. (2nd November 2017) - Ying, Le; Yan, Feng; Williams, Bryan RG; Xu, Ping; Li, Xin; Zhao, Yueling; Hu, Yiqun; Wang, Yuefei; Xu, Dakang; Dai, Jing
Summary: Epigallocatechin‐3‐gallate (EGCG) is a type of catechin. It exhibits excellent antioxidant effects and anti‐tumour activities for cancer chemoprevention. The mechanism of anti‐tumour effects of EGCG on different cancers has been studied for the past few decades, but remains controversial. To investigate the potential role that EGCG may play in the epigenetic regulation of colorectal cancer (CRC) cell line, we integrated bioinformatics analysis with experimental validation. We found that levels of the enhancer of zeste homologue 2 (EZH2) were significantly higher in CRC tissues compared to normal adjacent tissues, based on the Genomic Data Commons (GDC) data portal. Different human CRC cell lines exhibited differing expression of levels of the EZH2 protein. In RKO cells, EGCG and the EZH2 inhibitor GSK343 exhibited similar inhibitory efficacy on the proliferation, invasion and migration abilities of the cells, and suppressed protein expression of trimethylated lysine 27 on histone H3 (H3K27me3), which may be caused by the loss of the enzymatic function of EZH2. EGCG and GSK343 were found to have a synergistic effect on the growth of RKO cells in lower concentrations. EZH2‐correlated genes were enriched in the cell cycle pathway, the top‐ranking up‐regulated pathway in tumour tissues, based on pathway analyses using the Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Set Enrichment Analysis (GSEA). In accord with this, we confirmed that EGCG and GSK343 could both significantly arrest the G0/G1 phase in RKO cell cycle, suggesting EGCG and EZH2 inhibitor share a common mechanism of action in RKO cells.